Twelve-month contraceptive discontinuation, associated factors and its consequences in Nepal. - Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Contraceptive prevalence rate (CPR) remained stagnant in Nepal in the past ten years and Nepal failed to achieve the millennium development goals target on CPR in 2015. Since CPR is based on the use of contraceptives, it is extremely important to assess contraceptive discontinuation rates to find the reason for this stalemate in the country. Method: The 2016 Nepal Demographic and Health Survey contraceptive calendar data was used to get all the episodes of contraceptive use within one year. It was used to find discontinuation rates by methods, reasons, and associated factors. Pearson’s chi-square test was used to compare discontinuation rates across predictor variable categories and a multivariate logistic regression model was used to find independent factors of discontinuation rates. Result: Nepal reported a twelve-month contraceptive discontinuation rate of 64.4% along with higher discontinuation of modern methods (pill, intra-uterine device, injectable and male condom) and traditional methods (rhythm and withdrawal) than India and Bangladesh in 2016. Most women cited ‘side effects’ and ‘wanted more effective method” as the main reason for the discontinuation of modern methods whereas ‘method failure’ and ‘desire to become pregnant’ as the main reasons for the discontinuation of traditional methods. The bivariate analysis found age, province, education level, and wealth indices as the main predictor whereas multivariate analysis found province and education level as the independent factors of twelve-month discontinuation rates in Nepal. Conclusion: Stagnant unmet need for family planning and higher contraceptive discontinuation were responsible for the stagnation of the contraceptive prevalence rate in Nepal since 2006. Province and education were independent predictors of the twelve-month discontinuation rate in Nepal in 2016. Further analysis of discontinuation “while in need” is needed to assess the family planning plans, policies, and programs of Nepal at the national, provincial, and local levels to improve the contraceptive prevalence rate in the country.